Patterns of locoregional failure in locally advanced non-small cell lung cancer treated with definitive conformal radiotherapy: Results from the Gating 2006 trial. Issue 2 (February 2018) - Jouglar, Emmanuel; Isnardi, Vanina; Goulon, Dorothée; Ségura-Ferlay, Céline; Ayadi, Myriam; Dupuy, Claire; Douillard, Jean-Yves; Mahé, Marc-André; Claude, Line
Abstract: Purpose: To determine the patterns of locoregional failure (LRF) in patients with locally advanced non-small cell lung cancer treated with definitive radiotherapy (RT). Patients and methods: One hundred and fifty-four patients from the Gating 2006 prospective randomized trial were treated with conformal RT with or without respiratory motion management. For patients with a LRF as first event, treatment planning with simulation CT, pre-treatment 18 FDG PET-CT and post-treatment images demonstrating recurrence were registered and analyzed. Measurable LRF was contoured (rGTV) and classified as in-field, marginal, or out-of-field. Results: Median follow-up was 27.8 months. Forty-eight patients presented with LRF. One-year and 2-year locoregional disease-free survival rates were 77% (95% CI 70–83) and 72% (95% CI 64–79) respectively. 79% of the patients with LRF as first event relapsed within the RT field (55% isolated), 30% had marginal LRF component. Isolated out-of-field failure occurred in only 3% of all patients. The regions of highest FDG-uptake on pre-treatment PET-CT were located within the recurrence in 91% of patients with in-field LRF. Conclusion: In-field failure was the most common pattern of failure. Escalated dose RT with high-dose fractions guided by PET parameters warrants further investigation.